Placebo and Nocebo Effects in Motor Performance: An Overview of Reviews - Cayque Brietzke; Wesley Alves Ribeiro; Paulo Estevão Franco‐Alvarenga; Raul Canestri; Ìtalo Vínicius; Gustavo Vasconcelos; Julio Cesario; Nelson Carvas Junior; Vitor de Salles Painelli; Pires Flávio Oliveira (Brain and Behavior, 2025)
ABSTRACT Objectives To assess and synthesize the effect size and quality of the literature on the placebo and nocebo effects on motor performance and motor‐related perceptive responses. Design Umbrella review. Data sources Medline, Embase, Lilacs, Cochrane Database of Systematic Reviews for peer‐reviewed literature, PROSPERO for protocols, and the Open Access Theses and Dissertations for gray literature. Eligibility criteria for selecting studies Population—human participants with varied health conditions; intervention: placebo; control: no treatment or active intervention; outcome: motor performance (primary) and perceptual variables (secondary); study design—ystematic reviews with or without meta‐analysis. Results In total, 3432 records were gathered from searches, resulting in 13 eligible reviews after screening. These reviews encompassed 247 original studies, with 221 focusing on the placebo effect and 26 on the nocebo effect. Among all eligible systematic reviews, five conducted meta‐analysis with 5036 participants, and one provided a summary of effect sizes reported by the original studies with 1215 participants. The reviews reported small to large effects of placebo (SMD = 0.09–0.93) and nocebo (SMD = 0.37–1.20), and only two conducted the GRADE assessment. Conclusion We found varied placebo and nocebo effects on motor performance, likely due to the poor quality of the methodology used by most reviews, highlighting the need for well‐conducted systematic reviews on the placebo and nocebo phenomena.